مميزات تعدد اللغات في بناء عالم - محمد أزهر (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2017)
The Advantages of Multilingualism in Building a World. This paper is aimed at describing multilingualism In India, a country known with multilingual and multicultural people. India is the most multilingual country in the world and it is the second largest country with a population of more than 17 percent of the world's population. Knowing two or more than two languages becomes the need for communication among speech communities as well as individuals. Defined as an occurrence regarding an individual speaker who uses two or more languages, multilingualism basically arises due to the need to communicate across speech communities. Multilingualism is not a rare but a normal necessity across the world due to globalization and wider cultural communication. Also it is not a recent phenomenon; it was prevalent in the ancient time also. This means that the perspective of global citizenship has achieved a remarkable achievement. There is no doubt in history that India is one of the oldest civilizations and a source of other civilizations in the world and draws the attention of researchers, and is of great importance at the global level